Ready, Launch, Brand The Lean Marketing Guide for Startups. - Zeewy, Orly. (Milton : Productivity Press, 2021)
"A powerful and urgent introduction to lean marketing and the magic of getting it right." -- Seth Godin, author, This is Marketing You may be familiar with the Silicon Valley expression about the iterative approach to software development, "We're learning to fly the plane while we're building it." If so, think of a startup--with all its moving parts, phases, and personalities--as flying a plane, while you're building it, booking passengers, marketing the airline, interviewing co-pilots, and serving coffee. In this book, Orly Zeewy navigates the turbulence and provides a flight plan so you know when you've landed in the right airport. Orly Zeewy is a brand architect who helps startups cut through the noise. She has worked with dozens of founders and entrepreneurs to uncover their brands' DNA. In Ready, Launch, Brand: The Lean Marketing Guide for Startups you will learn how to close the marketing gaps that can slow down sales and make it harder to scale your business. Orly shares her brand process for building the right team, attracting brand evangelists, and cultivating a sustainable company culture. Prior to starting her brand consulting practice, Orly ran the award-winning Zeewy Design and Marketing Communications firm and directed marketing programs for national clients such as CIGNA, Kraft Foods, and Prince Tennis. She has lectured at the Wharton School of Business at the University of Pennsylvania, taught at the Charles D. Close School of Entrepreneurship at Drexel University, and been featured in the business section of the Philadelphia Inquirer.
Marketing ROI -- Measuring Marketing ROI -- The Bottom Line on Lean Marketing -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: New business enterprises; Marketing; Social media -- Marketing; Customer relations; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Management